Matka: Muteness, Metaphor, Metonymy - Quigley, Paula (My University, 2013)
To say that Matka presents us with essential truths about the human condition may sound trite at best. Nonetheless, the film’s very resistance to a reductive reading along these lines suggests the possibility of a specifically ‘metaphoric’ treatment of these truths that eludes articulation into language.
PUBLISHED
Keywords: metonymy; Peter Brooks; metaphor; ‘text of muteness’; Saara Cantell; melodrama